ANALISIS STABILITAS LERENG PADA TANAH CLAY SHALE PROYEK JALAN TOL SEMARANG-SOLO PAKET VI STA 22+700 SAMPAI STA 22+775 - Syafiq Alhadar; Luluk Asrida; Sri Prabandiyani; Siti Hardiyati (Jurnal Karya Teknik Sipil, 2014)
The aim of this thesis was to analyze the slope stability on clay shale soil and to provide recommendations of design that meet the design criteria with the level of service based on the standard on the project Semarang-Solo toll road. The toll road was built to support economic growth in Semarang, Solo and its surroundings. The location was reviewed in this thesis include a toll road project Semarang-Solo package IV Sta. 22+700 to 22+775. We choose these location because we consider that these sta have the greatest risk of landslides. The data used in this case study were primary and secondary datas. The datas were collected by interview method, observation methode and methods of literature. For analysing in this thesis were by calculate the slope stability and provide alternative solutions to problems that occured. Geotechnical analysis was done in two ways, namely manual and program. Manual analysis used Fellenius method and Bishop’s method while analysis finite element method used Plaxis software 8.2. Mohr-Coulomb failure model were chosen as a model soil. The results showed that the catastrophic landslide occurred at Sta 22+700 to 22+775. Changed the geometry of the slope and strengthening with bored pile at two different elevation were tired to produce sliding safety factor 1,433 this value is greater than the safety factor requirement 1,4.